Z vadbo do zdrave starosti - Dišič, Mitja (Šport (Ljubljana), 2024)
Aging leads to a decrease in muscle mass (sarcopenia), aerobic capacity, and functional abilities, increasing the risk of falls and loss of independence. Preserving fast-twitch muscle fibers is crucial, as they affect balance and the ability to perform rapid movements. Regular exercise, including aerobic activities, strength, and balance training, can slow or even prevent these changes. High-intensity interval training (HIIT) and high-load resistance training have proven particularly effective for older adults. HIIT enhances aerobic capacity and cardiovascular health in a shorter time than moderate-intensity exercise, while high-intensity resistance training safely increases muscle strength, power, and prevents bone density loss and functional decline. These training approaches are key for reducing frailty, preventing falls, and extending independence in older adults.
Keywords: aging; balance; cardiovascular health; functional ability; funkcionalna sposobnost; high-intensiti interval training; HIIT; independence; kardiovaskularno zdravje; neodvisnost; ravnotežje; resistance training; sport; staranje; šport; vadba proti uporu; visoko intenzivna intervalna vadba